WHY IS THERE CODE SWITCHING IN EFL CLASSROOM? : A CASE STUDY IN A VOCATIONAL SCHOOL IN CIMAHI WEST-JAVA - Fathimah, Diana Nur (Universitas Pendidikan Indonesia, 2016)
AbstractCode switching is a common phenomenon that results from the bilingual quality of a language speaker. In the educational context, code switching is frequently found in an EFL classroom of which the teacher is a non-native speaker. It is considered as one of the strategies to facilitate students to learn English more effectively. However, a number of research studies investigating EFL classroom discourse found various reasons of the use of code switching, ranging from the familiarity of the context to the teacher’s language proficiency. The present research gears toward investigating code-switching practiced by an EFL teacher in Indonesia and the rationale behind that practice. Taking case study method, this qualitative study employs observation and semi-structured interview to gather the data. An English teacher in one vocational school in Indonesia was chosen to be the participant of the research. The research shows that, as a bilingual, the teacher practiced code-switching both in educational context and non-educational context, inter-sententially and intra-sententially. In the classroom context, inter-sentential code switching was practiced deliberately to serve as exposures for students. Meanwhile, intra-sentential code switching was oftentime not a deliberate action, but rather a force of habit of the English teacher as a bilingual.Keywords: Bilingualism, code-switching, EFL classroomAbstrakAlih kode merupakan fenomena umum yang dihasilkan dari kualitas bilingual dari penutur bahasa. Dalam konteks pendidikan, alih kode sering ditemukan di dalam kelas EFL dimana guru merupakan pembicara non-pribumi. Hal ini dianggap sebagai salah satu strategi untuk memfasilitasi siswa untuk belajar bahasa Inggris dengan lebih efektif. Namun, sejumlah penelitian yang menyelidiki EFL wacana kelas menemukan berbagai alasan dari penggunaan alih kode, mulai dari keakraban konteks untuk kemahiran berbahasa guru. Penelitian ini bertujuan mengkaji alih kode yang dilakukan oleh seorang guru EFL di Indonesia dan alasan di balik praktek itu. Metode yang digunakan yaitu studi kasus, studi kualitatif dengan menggunakan observasi dan wawancara semi-terstruktur untuk memperoleh data. Seorang guru bahasa Inggris di salah satu sekolah kejuruan di Indonesia dipilih menjadi responden penelitian. Hasil penelitian menunjukkan bahwa, sebagai bilingual, guru berlatih alih kode baik dalam konteks pendidikan dan konteks non-pendidikan, antar-kalimat dan intra-kalimat. Dalam konteks kelas, alih kode antar-kalimat sengaja dipraktekkan untuk pengenalan awal bagi siswa. Sementara itu, kode intra-sentential sering kali dilakukan tidak disengaja, melainkan kebiasaan guru bahasa Inggris sebagai bilingual. Kata kunci: Bilingualism, alih kode, EFL kelas